Phytolith evidence suggests early domesticated rice since 5600 cal a BP on Hainan Island of South China. (28th December 2016) - Wu, Yan; Mao, Limi; Wang, Can; Zhang, Jianping; Zhao, Zhijun
Abstract: The prehistory of the domestication of rice in the tropical areas of South China is poorly understood. Here we present phytolith evidence recovered from a sediment core from the central-east coast of Hainan Island, China. The result of this study indicates that domesticated rice might grow on the Hainan Island in 5600 cal a BP. The early timing of rice domestication on Hainan Island supports the hypothesis of the spread rice agriculture from its origins in the Middle and Lower Yangtze River and its tributaries. Our results also highlight the practice of growing rice since 2000 years ago in the Lingnan region of the Nanyue Kingdom. The discovery of microfossil evidence such as phytoliths and starch grains should inspire more archaeological research that focuses on the origins and consequences of the spread of domestic rice agriculture to Hainan Island.